2017
DOI: 10.1093/nar/gkx339
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional mutagenesis reduces splicing fidelity in mammalian cells

Abstract: Splicing fidelity is essential to the maintenance of cellular functions and viability, and mutations or natural variations in pre-mRNA sequences and consequent alteration of splicing have been implicated in the etiology and progression of numerous diseases. The extent to which transcriptional errors or lesion-induced transcriptional mutagenesis (TM) influences splicing fidelity is not currently known. To investigate this, we employed site-specific DNA lesions on the transcribed strand of a minigene splicing re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 53 publications
1
11
1
Order By: Relevance
“…In agreement with earlier studies performed in vitro and in vivo ( 7 , 11 , 12 , 32 , 33 ), this work demonstrates that O 6 -meG is mutagenic during transcription. Furthermore, DNA repair wields a significant impact on the frequency of TM induced by O 6 -meG, an observation that has been made for other DNA lesions ( 9 , 12 , 33 , 34 ). As reported here, RNA-seq analysis indicated that 14.7% of p53 transcripts from cells lacking AGT activity contained a uridine misincorporation at codon 248, a number that was 100-fold lower in cells exhibiting AGT activity.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In agreement with earlier studies performed in vitro and in vivo ( 7 , 11 , 12 , 32 , 33 ), this work demonstrates that O 6 -meG is mutagenic during transcription. Furthermore, DNA repair wields a significant impact on the frequency of TM induced by O 6 -meG, an observation that has been made for other DNA lesions ( 9 , 12 , 33 , 34 ). As reported here, RNA-seq analysis indicated that 14.7% of p53 transcripts from cells lacking AGT activity contained a uridine misincorporation at codon 248, a number that was 100-fold lower in cells exhibiting AGT activity.…”
Section: Discussionsupporting
confidence: 92%
“…As reported here, RNA-seq analysis indicated that 14.7% of p53 transcripts from cells lacking AGT activity contained a uridine misincorporation at codon 248, a number that was 100-fold lower in cells exhibiting AGT activity. These numbers are lower than previously reported levels in vivo ( 11 , 12 ), which could be explained by the different cell systems used and/or the DNA sequence context of the lesion ( 35 ). The low levels of misincorporation (<1%) observed when AGT is active could reflect errors occurring during library preparation and sequencing ( 36 ).…”
Section: Discussioncontrasting
confidence: 81%
See 2 more Smart Citations
“…A. Paredes et al, 2017). For these reasons, we speculated that induction of oxidative stress by bisphenols could be responsible of observed transcriptional alteration as well as RNA splicing modification during meiosis initiation leading to prophase I defects.…”
Section: Badge or Bpaf Fetal Exposures Alter Dna Demethylation In Pgcsmentioning
confidence: 99%